University Libraries in Türkiye: Past to Present - A Comprehensive Analysis - Demir, Güler; Keseroğlu, Hasan Sacit (University and Research Librarians' Association, 2024)
University libraries play a vital role in the academic landscape by providing a wide range of essential support and services to their members. From research materials and academic resources to access to cutting-edge technology and expert staff, these libraries are at the forefront of fostering a culture of learning, collaboration, and innovation both within their physical spaces and online. Their importance extends beyond the academic environment, as they are also expected to contribute to the development of their respective countries by providing the resources and tools necessary to support a strong and thriving knowledge economy. The objective of this research is to provide a detailed analysis of the situation and challenges experienced by university libraries in Türkiye. This study utilized descriptive and documentary scanning methods to analyze and interpret data obtained from a wide range of both domestic and foreign literature, as well as official primary documents and media. The scope of the study was determined by historical, managerial, legal, and technological problems faced by Türkiye’s university libraries. To ensure systematic integrity, the study grouped various dimensions thought to have a direct or indirect impact on university libraries in Türkiye under different headings. These headings, which constitute the scope of the study, include: “Legislation, organization, and administrative structure”; “Policy, regulations, and standards”; “Budget, building, collection management, human resources, user-related matters, and other relevant issues”; “Collaborations”, and “Information and communication technologies”. By taking into account the historical context, this study aims to offer a comprehensive understanding of the issues that these libraries have faced and continue to face in the present day. The findings of this research indicate that the challenges encountered by university libraries in the past have yet to be effectively addressed and resolved. The study’s methodical, multifaceted, and multidimensional approach to evaluating university libraries, both in the historical context and current situation, presents a unique perspective. The comprehensive and in-depth evaluation process applied in this study is unparalleled and distinguishes it from prior studies in the field. This approach provides a holistic view of university libraries, allowing for a more detailed and accurate assessment of their overall performance.
Keywords: state university; H; private university; republic of türkiye; legislations; higher education; Social Sciences; foundation university; ottoman empire; university library; 4. Education